Pollution of bogs in Tomsk region (Western Siberia, Russia) as an indicator of sustainable development - Mezhibor, A.M (European Journal of Sustainable Development, 2014)
Wetlands play a key role in the climatic balance of our planet. Thus, their protection from anthropogenic pollution is an important target for sustainable development of environment. Wetlands have a special significance for the Siberian region of Russia where they take great territories. Peat bogs, being unique ecosystems among wetlands, have properties to save the history of atmospheric pollution. The particularity of peat bogs is determined by their nutrition - they receive chemical elements mostly from the atmosphere. Some peat bogs in Siberia (Tomsk region, Russia) were studied to determine the degree of environment pollution during the last century and the change of geochemical composition of peat in time. These studies determined the increase of pollution in the region from the middle of 20th century because of the sharp industrial development. The data on the pollution of peat bogs allow concluding that the geochemical peculiarities of different parts of Tomsk region influenced by different types of industry: nuclear facility, coal-burning power stations and oil refineries. This method can be used together with other methods implemented for the detection of anthropogenic pollution and the results can be used as indicative parameters in environmental change. The results of the studies can be used for the development of recommendations in the decrease of the industry influence for the sustainable development of Siberian region. Keywords: upland peat, air pollution, Tomsk region, indicators of sustainable development